ANALISIS BUDAYA ORGANISASI PADA BANK BNI SYARIAH CABANG KOTA LHOKSEUMAWE MENURUT KONSEP MANAJEMEN SYARIAH - Nur Sari Dewi; Hasmiati Hasmiati (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
The current business development has arrived the stage of global competition and open with the changes dynamics very quickly. In a global situation like this, All companies must create an organizational culture to bring in customers. Organizational culture is a confidence and behavior that determines how employees and a company's management interacts and resolves outside business transactions. The purpose of this research to determine the organizational culture at BNI Sharia branch of Lhokseumawe city and also according of sharia manajement concept. In this research used qualitative methods with descriptive approach. Data collection technique obtained via observation, interview and documentation, and then analyzed by using data reduction, data view and data verification. The research results shows that the implementation of organizational culture at BNI Sharia branch of Lhokseumawe city already according to sharia manajement concept. This is proven with the application of a work culture and congregation that can be trusted. Trust value is reflected from honest behavior and keeping promises, being responsible, excited to produce the best work, work sincerely and give priority to the intention of worshipand serve beyond expectations, while the value of pilgrims is reflected in the caring and courageous attitude of giving and receiving constructive feedback, building a professional synergy, share useful knowledge and understand the linkages of work processes and strengthen effective leadership. Keywords : Organizational Culture, Sharia Management.